2016
DOI: 10.1007/s13277-016-5348-8
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA UCA1 enhances tamoxifen resistance in breast cancer cells through a miR-18a-HIF1α feedback regulatory loop

Abstract: Recent studies reported that long non-coding RNAs (lncRNAs) might play critical roles in regulating endocrine resistance of breast cancer. Urothelial carcinoma-associated 1 (UCA1) is an lncRNA with an oncogenic role in breast cancer. This study aimed to investigate whether UCA1 is involved in acquired tamoxifen resistance in estrogen receptor (ER)-positive cancer cells. Our findings reveal that tamoxifen induces UCA1 upregulation in ER-positive breast cancer cells in a HIF1α-dependent manner. UCA1 upregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 37 publications
2
83
0
Order By: Relevance
“…[39] Another study showed that endogenous UCA1 knockdown significantly reduced the number of invading cells, suggesting that UCA1 upregulation increased the invasiveness of BC cells by activating Wnt/β-catenin signaling pathway. [40] Li et al [41] investigated the expression level of UCA1 in acquired tamoxifen resistance in estrogen receptor (ER)-positive breast cancer cells and argued that downregulation of UCA1 could enhance the sensitivity of breast cancer cells to tamoxifen resistance directly interact with miR-143. In contrast, Lee et al [42] suggest that special AT-rich sequence binding protein 1 is the upstream regulator of UCA1 expression and depletion of UCA1 could suppress tumor growth and cell survival of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[39] Another study showed that endogenous UCA1 knockdown significantly reduced the number of invading cells, suggesting that UCA1 upregulation increased the invasiveness of BC cells by activating Wnt/β-catenin signaling pathway. [40] Li et al [41] investigated the expression level of UCA1 in acquired tamoxifen resistance in estrogen receptor (ER)-positive breast cancer cells and argued that downregulation of UCA1 could enhance the sensitivity of breast cancer cells to tamoxifen resistance directly interact with miR-143. In contrast, Lee et al [42] suggest that special AT-rich sequence binding protein 1 is the upstream regulator of UCA1 expression and depletion of UCA1 could suppress tumor growth and cell survival of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen has been a mainstay chemotherapy utilized in breast cancer since its approval in the 1980s [457]. The lncRNA UCA1 has now been identified as a critical mediator of tamoxifen resistance in breast cancer by various mechanisms including sponging of miR-18a, a negative regulator of HIF1α [195], mTOR signalling [458], exosomal delivery of the lncRNA from resistant to sensitive cells [201], or via the Wnt/β-Catenin Pathway [190]. Other EMT associated lncRNAs which have been shown to affect tamoxifen sensitivity in breast cancer include MALAT-1 [99], lncRNA-ROR [459], and HOTAIR [460].…”
Section: Lncrnas Emt and Drug Resistancementioning
confidence: 99%
“…Tamoxifen is one of the major hormone therapies for endoplasmic reticulum positive breast cancer in clinical practice, and acquired resistance to tamoxifen remains a major obstacle in breast cancer treatment [110]. Tamoxifen treatment up-regulated expression of UCA1 in breast cancer cells through a miR-18a-HIF1a feedback loop [110].…”
Section: Breast Cancermentioning
confidence: 99%
“…Tamoxifen is one of the major hormone therapies for endoplasmic reticulum positive breast cancer in clinical practice, and acquired resistance to tamoxifen remains a major obstacle in breast cancer treatment [110]. Tamoxifen treatment up-regulated expression of UCA1 in breast cancer cells through a miR-18a-HIF1a feedback loop [110]. The overexpression of UCA1 conferred tamoxifen resistance by increasing the activity of Wntb-catenin signaling, which was accompanied by a decrease of miR-18a, an important modulator of cell cycle proteins [111,112].…”
Section: Breast Cancermentioning
confidence: 99%